2005
DOI: 10.1080/13693780412331282322
|View full text |Cite
|
Sign up to set email alerts
|

Common polymorphisms in critical genes of innate immunity do not contribute to the risk for chronic disseminated candidiasis in adult leukemia patients

Abstract: Chronic disseminated candidiasis is a serious fungal infection in immunocompromised patients, particularly those undergoing therapy for acute leukemia. Coordination between innate and adaptive immune system is critical to resistance or susceptibility to Candida infection. In order to investigate possible genetic contribution to chronic disseminated candidiasis of key molecules in the innate immune pathway, we performed a case control study using the candidate gene approach. Forty subjects with chronic dissemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…Indeed, in one study, a common haplotype of the IL-4 promoter was overrepresented in patients with CDC [31]. However, a study by the same group challenged this result by showing that common polymorphisms in 6 critical genes of innate immunity did not contribute to an increased risk of CDC [32].…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, in one study, a common haplotype of the IL-4 promoter was overrepresented in patients with CDC [31]. However, a study by the same group challenged this result by showing that common polymorphisms in 6 critical genes of innate immunity did not contribute to an increased risk of CDC [32].…”
Section: Discussionmentioning
confidence: 83%
“…This supports the existence of a 'healthy aging' phenotype in which individuals somehow delay or avoid major clinical disease and disability until late in life. Although previous studies have suggested that CHIT-1-deficient individuals show a certain degree of disadvantage, such as increased susceptibility to parasitic disease infections, to microorganisms containing chitin and to Gram-negative infections, 17,[31][32][33][34][35] other studies indicate that CHIT-1 deficiency is not a disadvantage but rather a selective advantage. [36][37] Given the very high gene frequency of the main mutant allele, as shown in this study, it seems more likely that in humans, selection has occurred in the direction of decreasing or eliminating the activity of this enzyme.…”
Section: Discussionmentioning
confidence: 94%
“…In our cohort candidemia was only detected in two patients, which might be related to early diagnosis and treatment or the more frequent use of pre-emptive antifungal treatment (18/89). Lastly, MBL2 variant alleles were similarly distributed in adult leukemia patients with and without chronic disseminated candidiasis in a third study (35).…”
Section: Discussionmentioning
confidence: 88%